An NK cell population lacking FcR? is expanded in chronically infected HIV patient - Zhou, J.; Amran, F.; Kramski, M.; Angelovich, T.; Elliott, J.; Hearps, A.; Price, Patricia; Jaworowski, A. (American Association of Immunologists, 2015)
We previously demonstrated that NK cells from HIV-infected individuals have elevated expression of activation markers, spontaneously degranulate ex vivo, and decrease expression of a signal-transducing protein for NK-activating receptors, FcR?. Importantly, these changes were maintained in virologically suppressed (VS) individuals receiving combination antiretroviral therapy (cART). In this study, we show that loss of FcR? is caused by the expansion of a novel subset of FcR?- CD56dim NK cells with an altered activation receptor repertoire and biological properties. In a cross-sectional study, FcR?- NK cells as a proportion of total CD56<suup>dim NK cells increased in cART-naive viremic HIV-infected individuals (median [interquartile range] = 25.9 [12.6- 56.1] compared with 3.80 [1.15-11.5] for HIV- controls, p < 0.0001) and in VS HIV-infected individuals (22.7 [13.1-56.2] compared with 3.80 [1.15-11.5], p = 0.0004), with no difference between cART-naive and VS patients (p = 0.93). FcR?-NK cells expressed no NKp30 or NKp46. They showed greater Ab-dependent cellular cytotoxicity activity against rituximab-opsonized Raji cells and in a whole-blood assay measuring NK responses to overlapping HIV peptides, despite having reduced CD16 expression compared with conventional NK cells. Their prevalence correlated with CMV Ab titers in HIV- subjects but not in HIV,+ individuals, and with the inflammatory marker CXCL10 in both groups. The expansion of a subset of NK cells that lacks NKp30 and NKp46 to ~90% of CD56dim NK cells in some VS HIV+ individuals may influence NK-mediated immunosurveillance in patients receiving cART.